Quantitative Impacts of Royalties on Mineral Projects - Lilford, Eric (Pergamon Press, 2017)
Policy-makers and legislators, typically representing a government body, are quick to impose royalties and other measures to secure income from natural resources operations. While this is undeniably appropriate, the question that is seldom asked by the same regulators is what impact does such an imposition beyond profit-based taxes have on the actual operation. Through taking away a percentage of the revenue that would otherwise have been due to the operation, what will the royalty do to the Resources-base, to the economic life of the operation, or to employment at the operation in the longer term? What royalty rate is optimal, being at what rate the operator pays and the government receives an equitable amount of revenue, and beyond what rate will the impact raise the possibility that the operator decides to discontinue operating? This paper introduces and quantifies a number of the impacts, including resources sterilisation, associated with royalties in the resources sector, using a gold operation as an example to outline the consequences of royalties based on revenue.